DEVELOPING STUDENTS’ INDEPENDENT THINKING THROUGH CREATIVE APPROACHES IN PRIMARY SCHOOL MOTHER TONGUE LESSONS (International journal of artificial intelligence, 2026)
This article examines the role of creative approaches in developing independent thinking skills among primary school students during mother tongue lessons. In modern education, it is essential to create learning environments that encourage students to think independently, express their ideas freely, and engage actively in the learning process. The study focuses on the pedagogical effectiveness of creative teaching strategies, such as problem-based learning, brainstorming, role-playing activities, and text-based creative tasks. The research findings indicate that lessons organized through creative methodologies significantly increase students’ cognitive engagement, improve their speech activity, and enhance their ability to analyze information independently. Furthermore, creative approaches contribute to the development of imagination, critical thinking, and decision-making abilities. As a result, integrating innovative teaching methods into primary school language education can positively influence students’ intellectual and communicative development.